Lactate Detection in Inducible and Orthotopic Her2/neu Mammary Gland Tumors in Mouse Models - Magnitsky, S. (2012)
The steady state concentration of lactate was compared in an inducible Her2/nue transgenic breast cancer mouse model and in tumors from the same Her2/neu model grown orthotopically. In vivo lactate was detected by MRS utilizing the Hadamard encoded selective multiple quantum coherence pulse sequence (HadSelMQC) recently developed by our laboratory (1). A lower lactate signal was observed in the inducible tumors than in the orthotopic tumors in vivo, while ex vivo analysis of perchloric acid extracts revealed similar amounts of this metabolite in both models. Histological staining of mammary tumor specimens demonstrated a much higher level of fat tissue in inducible tumors compared to the orthotopic model. Phantom studies with [3-(13)C] lactate indicated that the lipid environment can significantly reduce the T2 of lactate and impede its detection. The transgenic inducible model for breast cancer not only better recapitulates the biological aspects of the human disease, but also provides additional characteristics related to the in vivo detection of lactate that are not available in orthotopic or xenograft models. This study suggests that the level of lactate measured by the HadSelMQC pulse sequence may be underestimated in human patients in the presence of high lipid levels, which are typically encountered in the breast.